Japanese American internment : prisoners in their own land - Otfinoski, Steven (Tangled history., 2020)
Follows real people through the internment of Japanese Americans during World War II, discussing their evacuation, housing, time behind barbed wire, and life after the war. Features photographs, a timeline, a glossary, critical thinking questions, and further resources.